The role of intestinal gases in pediatric functional constipation: a narrative review of pathophysiology and emerging therapeutics - Zhou, Yuewen; Tao, Enfu (Frontiers in Nutrition, 2026)
Pediatric functional constipation (PFC) is a prevalent gastrointestinal disorder affecting approximately 18.2% of children worldwide, characterized by infrequent or painful bowel movements without organic cause, and significantly impairing quality of life, yet its management remains suboptimal. A central problem in its management is the high failure rate of conventional therapies; notably, treatments such as laxatives fail to achieve sustained relief in about 40% of pediatric patients, highlighting the critical need to explore novel pathophysiological mechanisms and therapeutic targets. Emerging evidence now highlights gut microbiota dysbiosis and the resulting imbalances in intestinal gases—particularly hydrogen (H₂), methane (CH₄), carbon dioxide (CO₂), and hydrogen sulfide (H₂S)—as key drivers of its pathophysiology. This review synthesizes current knowledge on how microbial gas metabolism influences gut motility in PFC: elevated CH₄, produced by methanogenic archaea such as Methanobrevibacter smithii, strongly correlates with delayed colonic transit and symptom severity, while H₂ enhances motility, and CO₂ and H₂S exert dose-dependent effects on peristalsis and mucosal signaling. Recent diagnostic advances, including H₂/CH₄ breath testing, electronic nose (E-nose) volatile organic compound profiling, and wireless motility capsules, enable non-invasive assessment of gas dynamics and transit, supporting precision phenotyping. Therapeutic strategies targeting gas-microbiota interactions—such as methane-lowering antibiotics (e.g., rifaximin), probiotics (e.g., Lactobacillus plantarum), low-fermentable oligosaccharides, disaccharides, monosaccharides, and polyols (FODMAP) diets, and neuromodulation—show promise, but pediatric-specific thresholds, safety, and long-term outcomes remain underexplored. The principal novelty of this review lies in its integrative framework, combining gastroenterology, microbiology, and engineering perspectives to advance gas-targeted precision medicine in PFC. Finally, we identify critical research gaps —such as the lack of pediatric-specific diagnostic thresholds and long-term therapeutic validation—and emphasize the urgent need for longitudinal studies and multidisciplinary trials to translate these insights into meaningful clinical outcomes.